Modeling the process of polymers processing in twinscrew extruders - Mikulionok, Ihor; Gavva, Oleksandr; Kryvoplias-Volodina, Liudmyla (Eastern-European Journal of Enterprise Technologies, 2018)
We developed a mathematical model of the process of polymer processing in co- and counter-rotating twin-screw extruders. The model takes into account a heat transfer of a polymer with screws and a barrel, as well as real boundary conditions (screws rotate, a barrel is stationary). We used the model of the allocated C-shaped volume, which is limited by one turn of cutting of each of screws and in which contains a volume of the processed polymer is located, for the analysis of the process. The model gives possibility to describe the process of processing both in the case of complete and partial filling of an operation channel with processed material. This is especially important in the case of dosed feeding of an extruder with a polymer, which is typical for modern extrusion equipment. We studied a temperature field of a polymer in operation channels of co- and counter-rotating twin-screw extruders and compared the results of the calculation with experimental data. We substantiated theoretically and confirmed experimentally, that, unlike in a single-screw extruder, it is necessary to heat operation elements firstly and to cool them then (in the direction from a loading funnel to an extrusion head) in a twin-screw extruder. We used the developed technique successfully at the development of modes of processing of various polymeric materials on co- and counter-rotating twin-screw extruders with screws of a diameter of 125 and 83 mm, respectively. The discrepancy between the calculated values and the experimental values of temperature at the outlet of a twin-screw extruder with co-rotation screws Ø83×30D does not exceed 10 %. The experimental value of the temperature somewhat exceeded the given value. We explain this by the fact that the system of thermal stabilization of working elements for the studied processing modes could not remove released heat of dissipation effectively. Application of the developed mathematical model will give possibility to forecast effective modes of operation of twin-screw extruders better, especially at processing of materials with low thermal stability.